2022
DOI: 10.1186/s40364-022-00407-y
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA 0009043 suppresses non-small-cell lung cancer development via targeting the miR-148a-3p/DNAJB4 axis

Abstract: Background Circular RNAs (circRNAs) are important regulators of the development and progression of non-small-cell lung cancer (NSCLC) and many other malignancies. The functional importance of circ_0009043 in NSCLC, however, has yet to be established. Methods The expression of circ_0009043, miR-148a-3p, and DnaJ heat shock protein family (Hsp40) member B4 (DNAJB4) in NSCLC cells was assessed via qPCR. The proliferative activity of these cells was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The nearby gene, DNAJB4 , is believed to be involved in regulating the growth of non-small cell LC. 37 Recent research reports that the deletion of this gene leads to a novel type of myopathy primarily characterised by early-onset respiratory failure. This suggests that DNAJB4 is closely associated with the development and progression of respiratory system diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The nearby gene, DNAJB4 , is believed to be involved in regulating the growth of non-small cell LC. 37 Recent research reports that the deletion of this gene leads to a novel type of myopathy primarily characterised by early-onset respiratory failure. This suggests that DNAJB4 is closely associated with the development and progression of respiratory system diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies on miR-148a-3p have revealed various downstream effects of modulating the levels or activities of miR-148a-3p. In addition to the promotion of angiogenesis, miR-148a-3p also inhibits the progression of malignancies such as hepatocellular carcinoma, lung cancer, and myeloid leukemia, besides exerting antifibrotic effects in pulmonary, liver, and atrial fibrosis. , Moreover, miR-148a-3p inhibits the inflammatory response and attenuates apoptosis in atherosclerosis to delay its progression. , The miR-148a-3p may also exert effects on skin wound healing by mediating other downstream effects and activating other signaling pathways, which requires further in-depth research.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that plasma SNORD83A could serve as a diagnostic biomarker for NSCLC. When combined with carcinoembryonic antigen, the diagnostic efficiency for early-stage NSCLC was significantly improved (Wang K. et al, 2022).…”
Section: Exosomal Snornas and Lung Cancermentioning
confidence: 99%